PELATIHAN PUBLISH OR PERISH, VOSVIEWER, DAN MENDELEY PADA MAHASISWA MBKM RISET FEB UNSOED - asmi ayuning hidayah; Indrawan Firdauzi; Joni Prayogi (Jurnal Pengabdian Bisnis dan Akuntansi Soedirman (JPBA), 2023)
MBKM Riset is one of the programs currently being implemented at FEB UNSOED with the goal of providing opportunities for students to increase their capacity, role, and participation, particularly in research activities that are relevant to their competencies. Some of the difficulties encountered by participants, such as how to identify research gaps, determine research titles, locate and manage references, and analyze and evaluate scientific publications, must be addressed immediately. The goal of this service activity is to provide training and assistance to all participants on how to optimize the use of Publish Or Perish, Vosviewer, and Mendeley in the preparation of research and scientific articles so that higher quality research can be produced. This activity's method consists of five stages: pre-survey, situation analysis and identification of partners' problems, problem-solving methods, PKM activity implementation, and evaluation. During the training and mentoring, participants were extremely enthusiastic. Participants felt the need for additional training as a result of the discussion, so that they could complete research results as efficiently as possible given the MBKM Riset timeline.